Critical Thinking and Multicultural Competence in Indian ELT: A Decolonial Approach - Nayar, A.C.V. (University of Jaffna, 2025)
The teaching of English in India exists at the intersection of colonial legacy, socio-economic stratification, and linguistic diversity. Despite on-going efforts to localize English Language Teaching (ELT), pedagogical practices often remain embedded in Eurocentric frameworks that marginalize indigenous knowledge systems and reinforce cognitive dependency on Western epistemologies. This paper argues that integrating critical thinking and multicultural competence into ELT can serve as a decolonial intervention, enabling students to navigate linguistic hierarchies, challenge cultural stereotypes, and assert their own epistemic agency. Drawing on recent developments in multicultural communicative competence, plurilingual pedagogy, and translanguaging practices, this study proposes a contextualized ELT framework that fosters intercultural awareness, reflective inquiry, and linguistic agency. The iceberg theory of culture and SIL International’s stages of cultural adaptation provide the foundation for designing a pedagogy that moves beyond surface-level understanding of English and encourages students to critically analyse the socio-political dimensions of the language. From a practitioner’s perspective, this study adopts a mixed-methods approach, incorporating: Classroom Ethnography – Observing interactions in multilingual Indian classrooms to identify cognitive and affective barriers to English learning; Action Research – Implementing critical thinking strategies such as Socratic questioning, dialogic teaching, and problem-posing education to encourage students to deconstruct colonial narratives within English texts; Curricular Analysis – Reviewing ELT textbooks from Indian educational boards and higher education institutions to examine how they either reinforce or challenge decolonial thought; Student Discourse Analysis – Evaluating students’ evolving perceptions of their linguistic identities through structured reflections and intercultural dialogue. The study anticipates that a critical thinking-driven, multicultural ELT pedagogy will lead to: Increased Student Agency – Learners will be able to critically assess and challenge linguistic and cultural biases within English texts and communication practices; Greater Intercultural Awareness – Moving beyond binary views of “native” vs. “non-native” English, students will develop confidence in Indian English as a legitimate linguistic identity; Epistemic Inclusion – The pedagogy will incorporate indigenous narratives and knowledge systems, making ELT a means of cognitive justice rather than cultural erasure; Plurilingual Competence – Learners will be able to navigate multiple linguistic codes fluidly, recognizing the role of English in a multilingual, multicultural society like India. By situating this research within the sub-theme of ‘Localizing the Teaching of English’, this paper advocates for a pedagogical shift from English as a colonial inheritance to English as a tool for intercultural dialogue and epistemic empowerment. The findings aim to inform curriculum design, teacher training programs, and classroom strategies that decentre English from its monolithic, colonial pedestal and reframe it as a dynamic, culturally negotiated practice in Indian classrooms.
Keywords: Critical thinking in ELT; Multicultural communicative competence; Plurilingual pedagogy; Translanguaging; Iceberg theory of culture